Trace mineral status of wall and sole portions of healthy and diseased hoofs in cattle and buffaloes - RANDHAWA, SWARAN S; DUA, K; SINGH, S T; RANDHAWA, C S (The Indian Journal of Animal Sciences, 2014)
Trace mineral composition of wall and sole portions of healthy and diseased hoofs was analyzed in cattle and buffaloes from organized and unorganized dairy farms. Hoof samples were collected from 10 animals each with healthy and diseased hoofs from each of the 4 groups (cattle-organized farms, cattle-unorganized farms, buffalo-organized farms, buffalo-unorganized farms). A significant high level of zinc and copper was observed in the wall portion as compared to sole portion in both healthy and diseased hoofs in cattle and buffaloes. The manganese and iron were significantly low in wall portion as compared to sole portion in healthy as well as diseased hoofs in both cattle and buffaloes. Although not much difference in the zinc levels of healthy and diseased hoofs from cattle and buffaloes was observed but buffaloes from unorganized farms have low hoof zinc levels as compared to those of organized farms. Significantly low copper levels were observed in diseased hoofs as compared to those of healthy in dairy cattle whereas high iron levels were observed in diseased hoofs as compared to healthy ones in dairy buffaloes. It was concluded that trace minerals do have a role in healthy horn synthesis.